Trends and Innovations in Character Building for Primary School Students in Indonesia - Bramianto Setiawan; Vina Iasha (Action Research Journal Indonesia (ARJI), 2024)
Character education and many negative events are the focus of conversation in education today. This condition emphasizes the need to develop and strengthen character values in learning. A literature review is needed to understand more about character-building research. This research aims to provide an overview of the geographical distribution of publications, trends and learning innovations in student character building in elementary schools. This research uses the Systematic Literature Review (SLR) method with the Preferred Reporting Items for Systematic Reviews And Meta-Analysis (PRISMA) model. The search was conducted through the Google Scholar database with the keywords "character building", and "character education" on January 10, 2024. The review results showed uneven research on character building for elementary school students in Indonesia, with the dominance of publication trends on the island of Java. Although the publication trend has increased since 2020, 2022, there has been a decline. In addition, innovations in character learning that involve habituation/models/learning media and school activities were identified. These results contribute to structuring more equitable and relevant character education policies across different regions in Indonesia and offer a foundation for developing more effective character learning innovations in primary schools.